Shifting Politics Between Muslim States & Israel: From the Khartoum Declaration to the Abraham Accords - Faheema, Nazhath (Universitas Islam Internasional Indonesia (UIII), 2023)
The Israel-Palestine conflict has long hindered diplomatic ties between Israel and many Arab and Muslim countries. However, a significant shift occurred in 1979, when Egypt normalised relations, followed by Jordan in 1994 and the Abraham Accords in 2020. These normalisation efforts signal a move from pan-Arab stance against Israel, based on the 1967 Khartoum Declaration, to a regional partnership driven by Arab states’ national interests. Despite establishing diplomatic relations, the need to achieve lasting stability and peace in the region necessitates addressing the Israel-Palestine issue comprehensively. The existence of an independent Palestinian state alongside Israel, ensuring safety for both Palestinians and Jews, is crucial. This imperative has become even more apparent in the 2023 Israel-Hamas war. Any renewed normalisation efforts between Arab states and Israel should learn from the precedents set in earlier waves of normalisation, but prioritising a better solution for the Israel-Palestine conflict is essential for the stability and peace in the Middle East.